Hematobiochemical changes of lead Poisoning and amelioration with Coconut (Cocos nucifera L.) Water in wistar albino rats - Enagbonma Ben Jesuorsemwen; Iyorah Imeda Ebikere; Iyorah Imeda Ebikere; Igiehon Nicholas Ozede; Aimuanmwosa Frank Eghomwanre (Journal of Applied Sciences and Environmental Management)
To determine the ameliorative effect of coconut water on haematobiochemical changes due to lead  poisoning in wistar albino rats for six weeks, sixty rats were assigned to four groups. 0.10g/l of lead  and 75ml coconut (cocus nucifera l.) water were given orally for six weeks. The mean values of red  blood  cells, mean corpuscular volume, mean corpuscular haemoglobin, mean corpuscular haemoglobin concentration, red blood cell distribution width and platelets  (8.10±0.63(×106μl), 52.7±0.87(μm3), 17.9±0.56(pg), 34.73±0.65(g/dl), 17.90±0.67(%) and 670.00±42.22(×103μl) respectively) reduced in lead treated rats when compared with control mean values (8.41 ± 0.90(×106μl), 56.60 ± 1.55(μm3), 19.33 ± 0.82(pg), 34.93 ± 0.90(g/dl), 18.27 ± 0.73(%) and  818.33± 123.68(×103μl) respectively ) and these values increased in75ml coconut water only group and the group of 0.10g/l lead + 75ml coconut water  except mean corpuscular haemoglobin, mean corpuscular haemoglobin concentration, and red blood cell distribution width of the 75ml coconut water only. The mean values of white blood cells, lymphocytes, total cholesterol, triglyceride, high density lipoprotein-cholesterol, low density lipoprotein-cholesterol, low  density lipoprotein-cholesterol/high density lipoproteincholesterol and total cholesterol/high density lipoprotein-cholesterol increased (12.23±0.57(×103μl),   79.83±3.87(%), 64.66±6.01(mg/dl), 89.00±7.94(mg/dl), 22.67±6.93(mg/dl), 21.00±4.58(mg/dl), 1.29±0.62 and 3.36±0.83 respectively ) in the lead group when compared with mean values of control group (5.83±0.74(×103μl), 69.07±10.57(%), 54.00±4.04(mg/dl), 97.33±11.34(mg/dl),   20.00±3.06(mg/dl), 17.00±6.51(mg/dl), 0.97±0.41 and 2.87±0.55 respectively) but the mean values decreased when compared with the mean values of group of 75ml coconut water only and group of 0.10g/l lead + 75ml coconut water, except the mean values of high density lipoprotein-cholesterol. These results indicate that coconut water could ameliorate effects of lead toxicity © JASEM